MINAT PELAJAR PUTRI SMA SE-KECAMATAN TELUK KERAMAT PADA KOMPETISI SEPAK BOLA DI KABUPATEN SAMBAS - Lestari, Meidyna Ayu; Triansyah, Andika; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research was how much interests of the female students of highschools in Teluk Keramat on football competition in the district of Sambas.This research intended to find out how much interests of the female students of highschools in Teluk keramat on football competition in the district of Sambas.The method used in this research was quantitative descriptive method with survey and the research instrument by using questionnaire. The data analysis technique used in this research was quantitative descriptive statistic by using percentages of data exposure. The population in this research were 284 female students of highschools in Teluk Keramat sub-district. The researcher used random sampling method in this research, with a total of 74 female students. The Result of the research showed that the interests of female students on football competition are in good category, with the average score of 3 in 77 percentage, each indicators had percentages as follows; good 65% of health indicator, good 68% of knowledge indicator, good 59% of talent indicator, very good 50% of happiness indicator, good 65% of environment indicator, good 57% parents indicator, good 62% of friends indicator, good 61% of achievement indicator. The conclusion of this research was that the female students of highschools in Teluk Keramat sub-district were interested on football competition in the district of Sambas.Keywords: Competition, Football, Interest